SUN-420 Pituitary Apoplexy Associated With Apixaban - Fanous, Nada (J Endocr Soc, 2019)
Background: Pituitary apoplexy (PA) is a relatively rare condition associated with sudden hemorrhagic pituitary infarction, and usually occurs in the setting of a pituitary adenoma. Patients typically present with the acute onset of headache, visual changes and pituitary hormonal deficiencies. Oral anticoagulation therapy is a known risk factor for PA and has recently been described in association with the newer anticoagulants, including both thrombin and Factor Xa inhibitors. Clinical Case: An 82 year-old woman with a history of renal cell carcinoma and recent post-operative pulmonary embolism treated with apixiban, presented with acute-onset headache, diplopia, and vomiting. Mental status remained intact. Vital signs were normal. Her physical exam was significant for a left superior temporal quandrantanopsia and was otherwise normal. Brain imaging revealed an 8 x 11 x 12 mm hyperdense mass within the sella representing hemorrhage. She had no known history of pituitary disease. The patient was admitted to the neurosurgical service for close monitoring of her neurologic and hemodynamic status. She was treated with conservative management and empiric glucocorticoids. Pituitary hormone assessment on admission was significant for inappropriately low LH of 0.5 mIU/mL (reference range 10-60) and FSH of 8.6 mIU/mL (reference range 17-114) in a postmenopausal woman. TSH was <0.03 mIU/L (reference range 0.4-5), and free T4 was elevated at 3.31 ng/dL (reference range 0.6-1.2). IGF-1 was within normal limits at 85ng/mL (reference range 31-208). Serum prolactin level was 13.7 ng/mL (normal <20). Cortisol and ACTH were measured after the patient had received empiric stress dose steroids and were thus unreliable. Of note, the patient did not exhibit signs or symptoms of adrenal insufficiency, such as hypotension or electrolyte derangements. Her headache and visual field deficit resolved with conservative treatment and she was discharged on physiologic glucocorticoid replacement therapy. Approximately two months after her initial presentation, the patient generally felt well except mild tremor and insomnia. Repeat endocrine evaluation confirmed central hypogonadism and primary hyperthyroidism. She was diagnosed with Graves’ disease and treated with methimazole. An ACTH stimulation test was normal and hydrocortisone replacement was discontinued. A repeat pituitary MRI demonstrated resolution of the hemorrhage and no evidence of a pituitary adenoma. Conclusion: Anticoagulation therapy, including the newer anticoagulants, is a risk factor for PA and is typically associated with an underlying pituitary tumor. To our knowledge, this is the first case of pituitary hemorrhage in a patient treated with apixaban without evidence of a pituitary tumor.